Secretario general interino del Comité Regional CNT de Cataluña en mayo 1937. on6x6/4228a. Original in CNT-collection
Secretario general interino del Comité Regional CNT de Cataluña en mayo 1937. on6x6/4228a. Original in CNT-collection.